2013
DOI: 10.1155/2013/983923
|View full text |Cite
|
Sign up to set email alerts
|

Oat Attenuation of Hyperglycemia-Induced Retinal Oxidative Stress and NF-B Activation in Streptozotocin-Induced Diabetic Rats

Abstract: The overproduction of reactive oxygen species (ROS) plays a central role in the pathogenesis of endothelial damage in diabetes. To assess the effect of oat on experimental diabetic retinopathy, five groups of Albino rats were studied: nondiabetic control, untreated diabetic, and diabetic rats treated with 5%, 10%, and 20% (W/W) oat of the diet for 12 weeks. Novel data were obtained in this study indicating a protective role of oat against oxidative stress and diabetic retinopathy. The effects of oat on paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
4
17
0
2
Order By: Relevance
“…NF-κB is well known to play pathological roles in both renal cells and diabetic kidney [50,51] and experiments have shown that blockage of NF-κB could possibly protect against diabetic renal damage [51, 52]. In addition, advanced glycation end products are known to activate NF-κB leading to its nuclear translocation [7]. In the present study treatment of diabetic rat with vitamin K1 produced decrease in NF-κB activation indicating possible nephroprotective mechanism.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…NF-κB is well known to play pathological roles in both renal cells and diabetic kidney [50,51] and experiments have shown that blockage of NF-κB could possibly protect against diabetic renal damage [51, 52]. In addition, advanced glycation end products are known to activate NF-κB leading to its nuclear translocation [7]. In the present study treatment of diabetic rat with vitamin K1 produced decrease in NF-κB activation indicating possible nephroprotective mechanism.…”
Section: Discussionsupporting
confidence: 53%
“…More importantly, reactive oxygen species (ROS) production in kidney is mainly due to increased activity of NADPH oxidase and superoxide production from mitochondria which leads to increase in metabolic activity and glycation of mitochondrial proteins [4,5]. In addition, DN has been shown to be associated with inflammatory changes involving increase in proinflammatory cytokines such as TNF, IL-12 etc., [6][7][8], reduction in anti-inflammatory cytokines, primarily IL-10 levels [9] and macrophage M1 predominance [3]. It is the activation and prevalence of macrophage M1 that is thought to drive the disease.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, AA could be converted to mediators such as PGs and LTs through oxygenation under oxidative stress. Previous studies found that oat could normalize the overproduction of reactive oxygen species (ROS) and reduce lipid peroxidation[34,35]. One possible explanation for the increased concentrations of AA in the oat bran groups might be reducing lipid peroxidation in dyslipedemic rats.…”
mentioning
confidence: 99%
“…Besides reduction of ROS overproduction, it also has an indirect AGE-inhibiting effect; it disrupts the detrimental AGE-RAGE-NF-kB pathways. Oat treatment also attenuated the increased VEGF and TNFa levels (Al-Malki, 2013).…”
Section: P1240mentioning
confidence: 91%
“…Besides reduction of ROS overproduction, it also has an indirect AGE-inhibiting effect; it disrupts the detrimental AGE-RAGE-NF-kB pathways. Oat treatment also attenuated the increased VEGF and TNFa levels (Al-Malki, 2013). Grape seed proanthocyanidin extracts (GSPEs) have been reported to possess a variety of potent properties including antioxidant, antiinflammation, radical scavenging, and antitumor activities (Houde et al, 2006;Shao et al, 2003;Vayalil et al, 2004).…”
mentioning
confidence: 99%